PURIFICATION AND CHARACTERIZATION OF WHITE RADISH (RAPHANUS SATIVUS L.VAR LONG WHITE) PEROXIDASE FROM CELL CULTURE EXTRACT - Pudjiraharti, -; Karossi, A.T. (Teknologi Indonesia, 2009)
Horseradish peroxidase (HRP) has been widely used as a component of clinical diagnostic reagent for Enzyme Linked I mmunosorbent Assay (ELISA) technique. White radish as one of Brassicaceae family members was found to have high peroxidase activity. In this study, white radish (Raphanus sativus L. var Long White) was used for the production of peroxidase by cell suspension culture technique. Isolation of the enzyme was conducted by ammonium sulfate precipitation followed by purification using DEAE-Cellulose column chromatography eluted with 0.01 M phosphate buffer, pH 7.5 and 0-0.5 M NaCl gradient. A major peak of protein having the highest enzyme activity and purity 25 folds compared to the crude was resulted. SDS-Polyacrilamide gel electrophoresis showed one main band with molecular weight of 47.000 Da. This white radish peroxidase enzyme is very efficient by demonstrating maximum activity at temperature 55oC and pH 7.5 as well as a Km 76.6 ?g/mL and V max 275 ?g/mL/minute toward hydrogen peroxide substrate and pyrogallol hydrogen donor.